Wagner: Bauman - Best, Shaun (Serendipities. Journal for the Sociology and History of the Social Sciences, 2021)
Book review of: Wagner, Izabela (2020) Bauman: A Biography. Cambridge: Polity Press 510 pp. ISBN: 978-1-5095-2686-4 Price: £25,00